Enactment of Sustainable Technovations on Healthcare Sectors - Geetika Madaan; Swapna H.R; ANUJ KUMAR; Amrinder Singh; Arokiaraj David (ACHSM, 2021)
This article discusses the use of innovative technologies and their potential to assist pan-India surveillance systems, including health  initiatives. The key goal is to review prior studies on innovative technology and its use for existing healthcare sectors and identify association strength among the selected variables using Vos Viewer software. Information gathered from research on randomized controlled trials, cross-sectional studies, review studies and systematic review studies, meta-analysis, sample, and case series. This article discusses the use of innovative technologies and their potential to assist pan-India surveillance systems, including health  initiatives to community based healthcare. This paper discusses the current usage of Artificial Intelligence, Blockchain, and the Internet of Things (IoT) on health and developments.   The findings of the study state the complexities and opportunities of the mentioned technologies on the pan-India health surveillance system and indicates that data management, safety and security regulation gaps need to resolve before enforcing monitoring practices. This paper presents an analysis of recent instances of using IoT technologies centred on remote surveillance and indicate a need for an advanced computing architecture for future integrated with pilot and tracking operations.